Identification of 39 stripe rust resistance loci in a panel of 465 winter wheat entries presumed to have high-temperature adult-plant resistance through genome-wide association mapping and marker-assisted detection - Yao, Fangjie; Wang, Meinan; See, Deven R.; Yang, Ennian; Chen, Guoyue; Chen, Xianming (Frontiers in Plant Science, 2025)
Stripe rust of wheat is a serious disease caused by Puccinia striiformis f. sp. tritici (Pst). Growing resistant cultivars is the most preferred approach to control the disease. To identify wheat genotypes with quantitative trait loci (QTL) for durable resistance to stripe rust, 465 winter wheat entries that were presumed to have high-temperature adult-plant (HTAP) resistance were used in this study. In the greenhouse seedling tests with seven Pst races, 16 entries were resistant to all the tested races. The 465 entries were also phenotyped for stripe rust responses at the adult-plant stage under natural infection of Pst in multiple field locations from 2018 to 2021 in the Washington state, and 345 entries were found to have stable resistance. The contrast of the susceptibility in the greenhouse seedling tests and the resistance in the field adult-plant stage for most of the entries indicated predominantly HTAP resistance in this panel. The durability of the resistance was demonstrated by a subset of 175 entries that were tested in multiple locations from 2007 to 2021. The 465 entries were genotyped through genotyping by multiplexed sequencing of single-nucleotide polymorphism (SNP) markers. Combining the stripe rust response and SNP marker data, a genome-wide association study (GWAS) was conducted, resulting in 143 marker–trait associations, from which 28 QTL that were detected at least with two races or in two field environments were identified, including seven for all-stage resistance and 21 for HTAP resistance. These QTL each explained 6.0% to 40.0% of the phenotypic variation. Compared with previously reported Yr genes and QTL based on their genomic positions, five QTL including two for HTAP resistance were identified as new. A total of 10 user-friendly Kompetitive allele specific PCR (KASP) markers were developed for eight of the HTAP resistance loci. In addition, molecular markers were used to detect 13 previously reported HTAP resistance genes/QTL, including two also identified in the GWAS analyses, and their frequencies ranged from 0.86% to 88.17% in the panel. The durable resistant genotypes, the genes/QTL identified, and the KASP markers developed in this study should be useful to develop wheat cultivars with long-lasting resistance to stripe rust.